The development of concept of arbitrability - an international comparison - Mrotzek, Carla (Department of Commercial Law, 2018)
The title of this dissertation is "The development of concept of arbitrability - an international comparison". In this dissertation I will compare the approach towards arbitrability in Germany, the United States of America and South Africa and how it developed until today. I will further give a brief overview of arbitrability in Europe and Africa. I will start by giving a brief introduction of arbitration and the definitions of objective and subjective arbitrability. In this dissertation I will only compare the development of objective arbitration. For every country I will first discuss the respective provision in the arbitration act and then discuss certain subject matters, which need further considerations. Arbitrability of some subject matters developed in a particular way either in legislation or jurisprudence, which need further explanation and some are handled in a separate statute. The term objective arbitrability describes the capacity of a subject matter to be resolves in arbitration. In former times arbitration was not seen as an appropriate alternative to jurisdiction and often prohibited. This changed over the past decades, which I will outline. In most countries in Europe and in the United States are close to no boundaries of arbitration anymore. African countries still have more restrictions, but also take a more liberal stand. Particular attention is amongst others brought to the following subject matters: intellectual property, antitrust, insolvency, family matters, labour law and consumer protection. In the United States and in South Africa subject matters which concerned public policy or involved public interests, such as antitrust, were restricted from arbitration for longer. This changed when legislators and jurisdiction gained trust in arbitral tribunals and statues and sets of rules for the conduction of arbitration were established. I will conclude that the general development to a greater scope of arbitrability is a welcomed progression. In the conclusion I will discuss the arbitrability of disputes involving public authority, family disputes and consumer and employers. In these areas arbitrability still needs further development.